Ventricular septal perforation naturally reduced in takotsubo cardiomyopathy. Issue 4 (April 2022) - Akiyama, Takumi; Okoshi, Yuki; Takano, Toshiki; Yoshida, Tsuyoshi; Tanabe, Yasuhiko
Abstract: An 80-year-old female was transferred to our hospital with dyspnea. Chest X-ray showed severe pulmonary congestion and electrocardiogram showed ST-segment elevation, abnormal Q, and negative T waves in leads V1–4. Transthoracic echocardiography demonstrated left ventricular apical akinesia with apical ventricular septal perforation. Emergent coronary angiography showed no coronary artery stenosis, and right-heart catheterization revealed a pulmonary to systemic flow ratio (Qp/Qs) of 2.2 on oximetry run. She was diagnosed with takotsubo cardiomyopathy with an associated complication of ventricular septal perforation. Her cardiac function gradually improved with nonsurgical treatment. An oximetry run performed 67 days later revealed that Qp/Qs decreased to 1.2. The size of ventricular septal perforation associated with takotsubo cardiomyopathy reduces naturally by conservative treatment, unlike that in acute myocardial infarction. <Learning objective: Ventricular septal perforation (VSP) has been reported as a rare complication of takotsubo cardiomyopathy (TCM). No specific treatment course has yet been established. The size of VSP associated with TCM may naturally reduce following conservative treatment, unlike that in acute myocardial infarction. Conservative treatment may be a better option if the patient is hemodynamically stable.>